1998
DOI: 10.1016/s0925-4773(98)00006-9
|View full text |Cite
|
Sign up to set email alerts
|

A POU protein regulates mesodermal competence to FGF in Xenopus

Abstract: XLPOU91, a POU-homeobox gene is expressed in a narrow window during early Xenopus development. We show that ectopic expression of XLPOU91 RNA causes severe posterior truncations in embryos without inhibiting the formation of Spemann's organizer. Ectopic XLPOU91 expression also inhibits mesoderm induction by fibroblast growth factor (FGF) and activin in animal cap explants. Using antisense RNA, we depleted endogenous XLPOU91 protein in animal caps. Gastrula-stage animal caps expressing XLPOU91 antisense RNA do … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 65 publications
2
31
0
Order By: Relevance
“…These results identify Oct3/4 as a factor contributing to the expression of the Cdx genes and actually activating one of the factors involved in its own repression. Several studies have shown that during gastrulation, the Xenopus Oct3/4 factors function in a manner consistent with the active maintenance of the pluripotent state like their mammalian homologues (Henig et al, 1998;Cao et al, 2006Cao et al, , 2007Morrison and Brickman, 2006;Snir et al, 2006). Thus, Cdx1 acting as a negative regulator of the Pou5f1 genes during gastrulation, would ultimately function to end the undifferentiated state and facilitate the transition into gastrulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results identify Oct3/4 as a factor contributing to the expression of the Cdx genes and actually activating one of the factors involved in its own repression. Several studies have shown that during gastrulation, the Xenopus Oct3/4 factors function in a manner consistent with the active maintenance of the pluripotent state like their mammalian homologues (Henig et al, 1998;Cao et al, 2006Cao et al, , 2007Morrison and Brickman, 2006;Snir et al, 2006). Thus, Cdx1 acting as a negative regulator of the Pou5f1 genes during gastrulation, would ultimately function to end the undifferentiated state and facilitate the transition into gastrulation.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies support the functional conservation between mouse Oct3/4 and the Xenopus Pou5f1 genes. The Xenopus Pou5f1 genes perform functions consistent with the maintenance of pluripotency, the regulation of gastrulation, the prevention of germ layer differentiation, and they can even maintain the pluripotency of mouse ES cells to different extents (Henig et al, 1998;Cao et al, 2006Cao et al, , 2007Morrison and Brickman, 2006;Snir et al, 2006). Also, the murine Oct3/4 protein can rescue the developmental malformations resulting from knock-down of the frog Pou5f1 gene activities (Cao et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…5C). GATA4 was detected, but not GATA5/6, Xhex, Chordin or Cerberus, which are all expressed in more anterior mesendoderm and involved in anterior patterning (Bouwmeester et al, 1996;Gove et al, 1997;Henig et al, 1998;Henry and Melton, 1998;Kelley et al, 1993;Smithers and Jones, 2002;Tao et al, 2005;Weber et al, 2000;Xanthos et al, 2001). Xwnt11, an anterior dorsalizing factor that lies upstream of Xhex activity, was not expressed in Nanos1-depleted PGCs.…”
Section: Fig 4 Nanos1-depleted Pgcs Exhibit Ctd-pser2 Prematurelymentioning
confidence: 99%
“…5C). Oct91, a homolog of Oct3/4 (Pou5f1) in mammals, functions as a pluripotent factor to preserve the uncommitted states of early blastomeres (Cao et al, 2007;Henig et al, 1998) and the germline (F.L. and M.L.K., unpublished) (Venkatarama et al, 2010).…”
Section: Expression Of Endoderm Genes In Nanos1 Morphantsmentioning
confidence: 99%
“…Like their mouse counterparts, they control pluripotency maintenance in embryos, suppressing BMP-mediated ventral fate acquisition, inhibiting Activin-and FGF-induced mesodermal commitment, and promoting neural tissue formation. This activity contributes to maintaining proper tissue boundaries and preventing expansion of mesodermal and endodermal territories into pluripotent ectoderm (Cao et al, 2006;Henig et al, 1998;Morrison and Brickman, 2006;Snir et al, 2006;Takebayashi-Suzuki et al, 2007).…”
Section: Introductionmentioning
confidence: 99%